Penerimaan Peserta Didik Baru (PPDB) Berbasis Website Yang Terintegrasi Dengan Aplikasi WhatsApp - M. Fathul Hidayat; Siti Sufaidah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The New Student Admission (PPDB) process is an essential part of school administration that requires speed, accuracy, and easy access for prospective students and their parents. At Yayasan Al Husna, the manual PPDB process has encountered various challenges, such as delayed services, data entry errors, and time and location constraints. This study aims to design and develop an Website-based PPDB system integrated with the WhatsApp application using native PHP and JavaScript programming languages. The system utilizes a chatbot technology capable of automatically interacting with users through WhatsApp messages, providing information, guiding the registration process, and recording student data in real time. The chatbot is developed with simple AI-based logic to understand user messages and respond according to context, without using any additional frameworks. The backend is built using native PHP, while the interface interaction and dynamic processing are handled with JavaScript. Implementation results show that this system improves the efficiency of the PPDB process, accelerates information services, and simplifies the school's task of managing registration data. Integration with WhatsApp provides user-friendly access without requiring additional applications, making it more inclusive for users from various backgrounds